ANALISIS PERKEMBANGAN MOTORIK HALUS USIA 5-6 TAHUN PADA ERA NEW NORMAL - Rachmi Marsheilla Aguss (Universitas Teknokrat Indonesia, 2021)
The purpose of this study aims to determine how the motor development of children aged 5-6 years in the new normal era. Six indicators are used as a description of fine motor skills in children aged 5-6 years. The method used in this research is the questionnaire method with the instrument used in the form of a questionnaire seen from the google form which is distributed through social media. The results of this study take subjects from the community who have children 5-6 years. The results showed the highest value of the six indicators was using writing utensils and cutlery correctly which reached an average value of 96% which was included in the percentage of excellent development. Then the indicator with the lowest score is drawing according to the idea which only contributes an average value of 76% into the percentage of expected development. Overall, the fine motoric development of children aged 5-6 years has a percentage of 84.6% that is included in the expected development criteria.